Multidimensional quantitative characterization of basal cell carcinoma by spectral- and time-resolved two-photon microscopy - Guo Fangyin; Lin Fangrui; Shen Binglin; Wang Shiqi; Li Yanping; Guo Jiaqing; Chen Yongqiang; Liu Yuqing; Lu Yuan; Hu Rui; He Jun; Liao Changrui; et al. (Nanophotonics)
Basal cell carcinoma (BCC) is a common type of skin cancer. Conventional approaches to BCC diagnosis often involve invasive histological examinations that can distort or even destroy information derived from the biomolecules in the sample. Therefore, a non-invasive, label-free examination method for the clinical diagnosis of BCC represents a critical advance. This study combined spectral- and time-resolved two-photon microscopy with a spectral phasor to extract rich biochemical information describing macroscopic tumor morphology and microscopic tumor metabolism. The proposed optical imaging technique achieved the rapid and efficient separation of tumor structures in systematic research conducted on normal and BCC human skin tissues. The results demonstrate that a combination of multidimensional data (e.g., fluorescence intensity, spectrum, and lifetime) with a spectral phasor can accurately identify tumor boundaries and achieve rapid separation. This label-free, real-time, multidimensional imaging technique serves as a complement to the conventional tumor diagnostic toolbox and demonstrates significant potential for the early diagnosis of BCC and wider applications in intraoperative auxiliary imaging.